CULINARY RECIPE AS A GENRE OF GASTRONOMIC DISCOURSE - Nurfaizieva Dilshoda Omonovna (Journals Park Publishing, 2022)
This article examines the history of gastronomy and culinary vocabulary of the German language, its features and its place in the modern world. The relevance of this problem is that knowledge of the laws, methods and means of word formation not only contributes to an overview of the entire range of a particular language in theoretical terms, but also has a direct practical value for mastering a foreign language. It will be possible to more accurately translate and express your thoughts.
Keywords: taste; discourse; nutrition